Piriformospora indica culture filtrate and cell extract induce chicoric acid production in Echinacea purpurea hairy roots - Samane Khalili; Ahmad Moieni; Naser Safaie; Mohammad Sadegh Sabet (PLoS ONE, 2025)
Echinacea purpurea (L.) Moench, commonly known as purple coneflower, is a significant medicinal plant renowned for its therapeutic properties, which are attributed to various phytochemical compounds, including caffeic acid derivatives (CADs). Chicoric acid is one of the CADs that has important immunostimulatory properties. This study employed a hairy roots (HRs) culture and an elicitation system to enhance the production of chicoric acid in E. purpurea. HRs cultures were established, and different concentrations (0, 1.25, 2.5, 5, and 10% v/v) of elicitors derived from Piriformospora indica culture filtrate (CF) and cell extract (CE) were added at two time points during the HRs growth period (on days 24 and 26). The effects of these treatments on the growth of HRs, chicoric acid production, and the expression of genes involved in the chicoric acid biosynthesis pathway were investigated. The highest dry weight of HRs (2.19 g/L, 1.36% higher than that in the control) was achieved in the HRs culture treated with 5% CF on the 24th day. In contrast, 5 and 10% (v/v) of P. indica CE, regardless of addition time, significantly decreased HRs growth compared to the control. The maximum production of chicoric acid (15.52 mg/g DW) was recorded after 48 h in the HRs culture treated with 5% CE on day 24, representing a 2.6-fold increase compared to the control (5.95 mg/g DW). Additionally, adding 2.5% CF to the HRs culture on day 26 resulted in a 2.3-fold increase compared to the control (13.5 mg/g DW) in chicoric acid biosynthesis. Real-time PCR assays revealed that the expression levels of the genes PAL, C4H, 4CL, C3H, and HCT were significantly upregulated after 3 and 12 h of elicitation with CE and CF. The highest gene expression was recorded for the C4H and PAL genes, 3 h after elicitation by CE (29.64 and 26.2-fold increases compared to the control culture). In contrast, the expressions of the 4CL and C3H genes peaked 12 h after elicitation with CF. The expression of the HCT gene also reached its highest level after 12 h of CE elicitation. Consistent with the chicoric acid production results, CE was found to be a more effective elicitor for inducing gene expression in the chicoric acid biosynthesis pathway. Overall, these findings indicate that HRs cultures and elicitors derived from P. indica are promising strategies to enhance chicoric acid production in E. purpurea (L.).